Job Satisfaction and Professional Stress Among University Teachers - Poudel, Guru Prasad (Gipan, 2025)
Teaching is a constant guidance and support to the students for learning and developing competencies. Teachers should display caring attitude and facilitate in all possible ways. The aim of teaching is to encourage in learning, encourage in knowledge generation and develop skills and attitudes. Teaching is a profession and teachers should be professionals. The professionals are expected to adhere established principles, such as maxims of order, involvement, encouragement, consistency, support, accuracy, and efficiency (Richards, 1996), and showcase high standards of conduct. People may hold different views on teaching, for instance, some may perceive it as easier job and everyone can easily handle, however, but I experience it as a job of mix emotions, including series pleasant and panic moments. In this regard, this study was conducted aiming at exploring the state of job satisfaction, professional stress and role of language in the university teachers’ professional discourse. The data was elicited from the narratives of five purposively selected English language teachers teaching in the different constituent campuses of Tribhuvan University. Under the philosophy of interpretivist approach, a qualitative method was applied for the research and narrative interview was used as the technique for data collection. The thematic interpretation of the narratives entailed that university level English language teachers, though they have enthusiasm to be better scholars, have been facing both professional and work-force related stress. They find teaching stressful nowadays due to institutional policies related to performance evaluation and their financial security from the job. The findings enable me to conclude that the university leaderships should revisit the criteria of teacher performance evaluation and devise policies for better workplace environment and motivation.